STRATEGI PEMASARAN TABUNGAN PRIMA BERHADIAH DALAM PENINGKATAN MINAT MENABUNG NASABAH BANK MUAMALAT INDONESIA KCP SUMENEP - Holilur Rahman; Ulfa Nur Sakinah; Dianawati Bt Mat Romli; Fatin Najwa Nazurah (Bayan lin-Naas : Jurnal Dakwah Islam, 2021)
Prima savings products with prizes have liquid fund benefits where customers can withdraw their funds, safe, convenient and profitable. This is in accordance with the existing theory where, the pricing strategy offers a fairly high percentage of profit sharing even equivalent to deposits. The purpose of this study was conducted to find out how the marketing strategy of Tabungan Prima Berhadiah in attracting customers to make savings using Tabungan Prima Berhadiah. The results of this study show that the strategy carried out by Bank Muamalat KCP Sumenep in increasing customer interest in saving is to determine the target market, cross-selling, mouth to mouth, and utilize technology networks.